1990
DOI: 10.2165/00007256-199010020-00006
|View full text |Cite
|
Sign up to set email alerts
|

Knee Injuries in Volleyball

Abstract: The knee is the most frequent site of injury in volleyball players. More than 40% of high level players suffer overuse injuries during this activity; this particularly painful syndrome is caused by the amount of jumping typical in volleyball play, and in its training which aims at strengthening the quadriceps muscle. In volleyball players the extensor apparatus is subject to continuously high stress and the bone tendon junction, being the weakest point, is susceptible to lesion. The prevention and treatment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 11 publications
1
44
0
1
Order By: Relevance
“…23,24 Individuals who participate in sports that subject joints to more intense impact and torsional loading than running does may have an increased prevalence of osteoarthritis. 19,21,38,58 Participants in American football appear to have an increased incidence of degenerative change in multiple joints, possibly due to joint injuries. 21,76,97,105 One investigator reported that more than 80% of American football players with a histor y of a knee injur y had evidence of osteoarthritis 10 to 30 years after competing.…”
Section: Sports and Posttraumatic Osteoarthritismentioning
confidence: 99%
“…23,24 Individuals who participate in sports that subject joints to more intense impact and torsional loading than running does may have an increased prevalence of osteoarthritis. 19,21,38,58 Participants in American football appear to have an increased incidence of degenerative change in multiple joints, possibly due to joint injuries. 21,76,97,105 One investigator reported that more than 80% of American football players with a histor y of a knee injur y had evidence of osteoarthritis 10 to 30 years after competing.…”
Section: Sports and Posttraumatic Osteoarthritismentioning
confidence: 99%
“…These results show that muscle flexibility is high at this age in female athletes generally. This study's finding of high muscle flexibility using the heel-tobuttock and SLR tests among flexible female athletes is thought to be due to the fact that subjects' skeletal growth had stopped, because they were well past their growth period, and their longitudinal muscle growth had had time to catch up with skeletal growth, and also because the subjects were older than these of other studies 1,2,6) .…”
Section: Buttocks Rising Test and Muscle Flexibilitymentioning
confidence: 69%
“…Although volleyball is the sport with the highest incidence of jumper's knee overseas as well as nationally 5) , most published literature on the subject does not classify cases by factors such as gender or age 1,2,[6][7][8][9][10][11][12][13][14][15][16] . Generally, male athletes have higher jumping power and lower muscle flexibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patellar tendinopathy has been reported as the most common injury in volleyball, representing as much as 28% of the injuries in that sport. 4,14 Ferretti et al 4 reported an incidence as high as 40% among high-level volleyball players. Patellar tendinopathy can be debilitating to an athlete, resulting in limited participation or cessation of play.…”
mentioning
confidence: 99%